2016
DOI: 10.1002/jbt.21874
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of ZEA cytotoxicity to mouse endometrial stromal cells and RNA-seq analysis

Abstract: Because zearalenone (ZEA) causes harmful influence to animals and widely exists in the world, the researches on ZEA have never stopped. However, the mechanisms of ZEA on proliferation, cycle, and apoptosis in endometrial stromal cells (ESCs) remain poorly defined. Therefore, the purpose of our study was to explore the effects of ZEA to ESCs and demonstrate them by transcriptomic analysis. The results showed that after ZEA treatment, ESCs appeared numerous adverse reactions, and the phenomena of cell viability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Our results demonstrated that ZEA dramatically decreased the growth of porcine granulosa cells in a dose and time dependent manner, and caused a significant increase in apoptotic cells. It was of note that in a previous report from other groups, ZEA exposure led to apoptosis in porcine splenic lymphocytes, immortalized goat Leydig cells, and endometrial stromal cells 32 , 47 , 48 . Next, ZEA exposure considerably altered the mRNA expression of genes in the granulosa cells using an RNA-seq approach, and the DEGs were found to be involved in cellular processes, molecular functions, and biological processes that were closely associated with cell proliferation, cell cycle, apoptosis, and DNA damage repair.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our results demonstrated that ZEA dramatically decreased the growth of porcine granulosa cells in a dose and time dependent manner, and caused a significant increase in apoptotic cells. It was of note that in a previous report from other groups, ZEA exposure led to apoptosis in porcine splenic lymphocytes, immortalized goat Leydig cells, and endometrial stromal cells 32 , 47 , 48 . Next, ZEA exposure considerably altered the mRNA expression of genes in the granulosa cells using an RNA-seq approach, and the DEGs were found to be involved in cellular processes, molecular functions, and biological processes that were closely associated with cell proliferation, cell cycle, apoptosis, and DNA damage repair.…”
Section: Discussionmentioning
confidence: 79%
“…The ATM pathway is responsible primarily for DNA-DSBs, ZEA exposure induced oxidative DNA-DSBs and the expression of ATM, and an increase in the concentration of ZEA further increased DNA damage 24 , 31 . It has been found that ZEA can arrest the cell cycle at S and G2/M phases to block DNA replication in some somatic cells of the reproductive system 32 . However, it is unknown the influence of ZEA on genomic stability of ovarian granulosa cells which played vital roles during oocytes growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…While BCL-2 guards against apoptosis, BAX is a promoter of apoptosis and a higher BAX/BCL-2 ratio favors a greater rate of apoptosis. Xie, Hu [ 118 ] also reported decreased cell viability in mouse endometrial stromal cells after ZEN exposure (>50 µM). Other cytotoxicity markers were enhanced including cell shrinkage, disruption of the cell cycle, and differential expression of genes related to cell cycle and apoptosis such as Bec-2 family , Cdc genes and Hoaxa-10 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, recent studies in porcine endometrial cells indicate that ZEN can activate the WNT/β-catenin signaling pathway to promote proliferation [ 123 ]. Overall, the evidence from murine models points toward strong apoptotic effects of mycoestrogens in the uterus and decreased cell viability in endometrial stromal and granulosa porcine-derived cells [ 101 , 118 , 120 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cells were exposed to 75, 100, 125 μM ZEA for 24 hours according to the previous experimental results, and they correspond to experimental group 1 (EG1), experimental group 2 (EG2), and experimental group 3 (EG3), respectively. In the experiments, dimethyl sulphoxide (DMSO) as the solvent reagent of ZEA.…”
Section: Methodsmentioning
confidence: 99%